Challenges and limtations of site specific crop production applications of wheat and maize - Balla, István; Tarnawa, Ákos; Horváth, Csaba; Kis, Judit; Jolánkai, Márton (Acta Agraria Debreceniensis, 2012)
The development and implementation of precision agriculture or site-specific farming has been made possible by combining the Global Positioning System (GPS) and the Geographic Information Systems (GIS). Site specific agronomic applications are of high importance concerning the efficiency of management in crop production as well as the protection and maintenance of environment and nature. Precision crop production management techniques were applied at four locations to evaluate their impact on small plot units sown by wheat (Triticum aestivum L.) and maize (Zea mays L.) in a Hungarian national case study. The results obtained suggest the applicability of the site specific management techniques, however the crops studied responded in a different way concerning the impact of applications. Maize had a stronger response regarding grain yield and weed canopy. Wheat was responding better than maize concerning plant density and protein content performance.